The fertility rebound and economic growth. New evidence for 18 countries over the period 1970-2011 - Piotr Dominiak; Ewa Lechman; Anna Okonowicz (Gdańsk University of Technology, Faculty of Management and Economics, 2014)
The long-run impact of economic growth on total fertility trends is ambiguous and sensitive for in-time variations. Over last decades, economic growth has led in many countries to significant falls in total fertility rates. However, in recent years, in high-income economies a kind of “fertility rebound” is revealed (Goldstein 2009; Luci and Thevenon, 2010; Day 2012). The concept of fertility rebound supports the hypothesis that reversal trends in total fertility rates are mainly attributed to economic growth. The paper unveils the relationship between total fertility rate changes and economic growth in 18 selected countries with fertility rebound observed, over the period 1970-2011. We anticipate uncovering U-shaped impact of economic growth on total fertility rate. To report on the relationship we deploy longitudinal data analysis assuming non-linearity between examined variables. Data applied are exclusive derived from World Development Indicators 2013. Our main findings support the hypothesis on U-shaped relationship between total fertility rate and economic growth in analyzed countries in 1970-2011. Along with the previous we project the threshold level of GDP per capita when the fertility rebound takes place.
Keywords: J11; O10; C23; 330; fertility rate; fertility rebound; economic growth; panel data analysis